Advances in Industry 4.0 : Concepts and Applications (Smart Computing Applications ,, 2022)
This book presents the emerging technologies of Industry 4.0. It describes the growing trend towards automation and data exchange in the manufacturing industry, with a focus on the internet of things (IoT), the industrial internet of things (IIoT), cyberphysical systems (CPS), smart factories, cloud computing, cognitive computing, and artificial intelligence.